المنظمات الدولية ودورها في تحقيق الأمن البيئي - توفيق عثامنية; عز الدين طالب (My University, 2025)
Abstract International organizations are among the most prominent actors on the global stage when it comes to environmental protection and achieving environmental security. Environmental issues such as climate change, desertification, biodiversity loss, and pollution of natural resources have become shared challenges that transcend national borders and require coordinated collective responses. This is where the role of international organizations—such as the United Nations Environment Programme (UNEP), the Food and Agriculture Organization (FAO), the World Health Organization (WHO), and the International Union for Conservation of Nature (IUCN)—comes into play. These organizations work to strengthen cooperation among countries, formulate environmental policies, and monitor compliance with international agreements such as the Paris Agreement on climate change. They also provide technical and financial support to developing countries in facing environmental challenges and play an awareness-raising and motivational role in guiding efforts toward sustainable development. Through these integrated efforts, international organizations aim to establish environmental security as a fundamental component of overall human security, ensuring the sustainability of natural resources and the protection of the planet for future generations. ........................ الملخص تُعد المنظمات الدولية من أبرز الفاعلين في الساحة العالمية عندما يتعلق الأمر بحماية البيئة وتحقيق الأمن البيئي. فقد أصبحت القضايا البيئية، مثل التغير المناخي، التصحر، فقدان التنوع البيولوجي، وتلوث الموارد الطبيعية، تحديات مشتركة تتجاوز الحدود الوطنية وتتطلب استجابة جماعية منسقة. وهنا يأتي دور المنظمات الدولية، مثل برنامج الأمم المتحدة للبيئة (UNEP)، ومنظمة الأغذية والزراعة (FAO)، ومنظمة الصحة العالمية (WHO)، والاتحاد الدولي لحماية الطبيعة (IUCN)، التي تسعى إلى تعزيز التعاون بين الدول، وصياغة السياسات البيئية، ومراقبة الالتزام بالاتفاقيات الدولية كاتفاقية باريس للمناخ، حيث تسهم هذه المنظمات في دعم الدول النامية تقنيًا وماليًا لمواجهة التحديات البيئية، كما تلعب دورًا توعويًا وتحفيزيًا في توجيه الجهود نحو تحقيق التنمية المستدامة. من خلال هذه الجهود المتكاملة، تسعى المنظمات الدولية إلى ترسيخ الأمن البيئي كعنصر أساسي في الأمن الشامل للبشرية، بما يضمن استدامة الموارد الطبيعية وحماية كوكب الأرض للأجيال القادمة. ........................... Résumé Les organisations internationales comptent parmi les acteurs les plus importants sur la scène mondiale en matière de protection et de sécurité de l'environnement. Les problèmes environnementaux, tels que le changement climatique, la désertification, la perte de biodiversité et la pollution des ressources naturelles, sont devenus des défis communs qui transcendent les frontières nationales et nécessitent une réponse coordonnée et collective. C'est là qu'interviennent les organisations internationales telles que le Programme des Nations Unies pour l'environnement (PNUE), l'Organisation des Nations Unies pour l'alimentation et l'agriculture (FAO), l'Organisation mondiale de la santé (OMS) et l'Union internationale pour la conservation de la nature (UICN). Ces organisations cherchent à renforcer la coopération entre les pays, à formuler des politiques environnementales et à veiller au respect des accords internationaux tels que l'Accord de Paris sur le climat. Elles contribuent à soutenir techniquement et financièrement les pays en développement pour relever les défis environnementaux, et jouent également un rôle de sensibilisation et de motivation en guidant les efforts vers un développement durable. Par ces efforts intégrés, les organisations internationales cherchent à faire de la sécurité environnementale une composante fondamentale de la sécurité humaine globale, garantissant la durabilité des ressources naturelles et la protection de la planète pour les générations futures.
Keywords: Keywords International Organizations; Environmental Security; International Cooperation; الكلمات المفتاحية : المنظمات الدولية ، الأمن البيئي ، التعاون الدولي ، الحماية البيئية ، التنمية المستدامة،الاتفاقيات الدولية; Mots-clés : Organisations internationales; sécurité environnementale; coopération internationale; protection de l'environnement; développement durable; accords internationaux